2014
DOI: 10.1002/ajmg.a.36706
|View full text |Cite
|
Sign up to set email alerts
|

Informed consent for exome sequencing research in families with genetic disease: The emerging issue of incidental findings

Abstract: Genomic sequencing technology is increasingly used in genetic research. Studies of informed consent for exome and genome sequencing (ES/GS) research have largely involved hypothetical scenarios or healthy individuals enrolling in population-based studies. Studies have yet to explore the consent experiences of adults with inherited disease. We conducted a qualitative interview study of 15 adults recently enrolled in a large-scale ES/GS study (11 affected adults, four parents of affected children). Our study had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…As such, inpatient pretest counseling was historically not provided by GCs. However, rES trio testing requires complex coordination and thorough pretest counseling, complicated by psychosocial considerations for parents of critically-ill infants (Bergner et al, 2014;Clift et al, 2015;Cornelis et al, 2016;Frankel, Pereira, & McGuire, 2016;Roche & Berg, 2015;Sapp et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As such, inpatient pretest counseling was historically not provided by GCs. However, rES trio testing requires complex coordination and thorough pretest counseling, complicated by psychosocial considerations for parents of critically-ill infants (Bergner et al, 2014;Clift et al, 2015;Cornelis et al, 2016;Frankel, Pereira, & McGuire, 2016;Roche & Berg, 2015;Sapp et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This interest in receiving all results has also been observed among patients undergoing clinical diagnostic exome sequencing (28). Bergner et al (2014) suggested that individuals living with a genetic condition may feel that they are adequately prepared for additional genetic risks (17). However, other studies have shown that some participants distinguish between different types of results (18).…”
Section: Discussionmentioning
confidence: 99%
“…The need for such data has been emphasized as a crucial step to effectively implement WES in undiagnosed disorders (Facio et al 2014). Thus far, however, publications on parental/patient perspectives on WES have mostly focused on secondary/incidental findings (Abdul-Karim et al 2013;Bergner et al 2014;Clayton and McGuire 2012;Clift et al 2015;Green et al 2013;Hegde et al 2015;Jarvik et al 2014). The few studies that have examined parental perceptions of the primary WES results in childhood undiagnosed disorders reported that parents expressed a sense of responsibility in needing to pursue the WES and had positive expectations about learning the results (Krabbenborg et al 2016;Sapp et al 2014).…”
Section: Introductionmentioning
confidence: 99%